PENGARUH PENERAPAN MODUL KONSELING NIFAS TERHADAP PENINGKATAN PENGETAHUAN, SIKAP, DAN KETERAMPILAN KONSELING BIDAN - Risna Fazlaini (Jurnal Medikes (Media Informasi Kesehatan), 2020)
One of the competencies of midwife is responsible to give care during the postpartum period according to women’s individual need. In providing postpartum care, midwives should be able to detect of complications, thereby reducing morbidity and maternal mortality. Counseling is one of the interventions that can be given to the mother. Postpartum counseling module is a module that was designed and compiled based on literature review as a guide to help midwives provide counseling on postpartum mothers. The aim of the study is to analyze the effect of implementation of postpartum counseling module to increase knowledge, attitudes and counseling skills of midwives. The study is analitic with quasi experimental with pretest-posttest control group design. A sample size of 42 people that divided into two groups, 21 people in intervention group and 21 people in control group using stratified random sampling technique in the period January 16-February 25, 2017 conducted in Tegal. Data were analyzed by using t-test to examine the average increase scores of knowledge, attitudes and skills before and after training module on intervention group and before and after submission of KIA book in the control group. Mann-Whitney test to analyzed the comparison of the average increase score of knowledge, attitude and skills of midwives between the two groups. Instrument which is used in this study were questionnaire to measure knowledge and attitudes and observation sheet to assess the counseling skills of midwives The result showed that the average increase in score of knowledge 50% (p<0,05), attitude 40% (p<0,05), and midwife counseling skill 99,7% (p<0,05) in the treatment group is higher than control group with percentage increase of 0% (p>0,05) on knowledge, 0% (p>0,05) on attitude and 0% (p>0,05) on skills. The conclusion is score of knowledge, attitudes and skills of midwife counseling in the treatment group higher than control group. The optimal use of the postpartum counseling module by midwife is expected to improve the quality care in counseling during postpartum period. Keyword: Attitude, Counseling, Module, Knowledge, Skill, Postpartum